The mitochondrial transport protein SLC25A43 affects drug efficacy and drug-induced cell cycle arrest in breast cancer cell lines - GABRIELSON, MARIKE (D.A. Spandidos, 2013)
The mitochondria have been identified as key players of apoptosis, cell proliferation and cell cycle regulation. However, the role of mitochondria in breast cancer and treatment failure remains unclear. We have previously shown a common deletion of the gene SLC25A43 in human epidermal growth factor receptor 2 (HER2)-positive breast cancer. This gene is coding for a mitochondrial inner membrane transporter and, to date, little is known about the function of this protein. We have also found that low protein expression of SLC25A43 significantly correlates with a lower S phase fraction in HER2-positive breast cancer. The aim of this study was to investigate whether knockdown (KD) of SLC25A43 could have an effect on the cytotoxicity of different cytostatic drugs using MCF10A, MCF7 and BT-474 cells. Following siRNA-mediated KD of SLC25A43, one non-malignant and two breast cancer cell lines were exposed to the anthracycline epirubicin or the taxane paclitaxel. The HER2-positive breast cancer cells were also exposed to the targeted therapy trastuzumab and dual exposure to trastuzumab and paclitaxel. We found that KD of SLC25A43 resulted in a decreased cytotoxic effect of paclitaxel in the two cancer cell lines (P<0.05). Further analysis of cell cycle phase distribution showed that KD increased the paclitaxel-induced G2/M block in these two cell lines (P<0.05). KD of SLC25A43 also reduced the inhibitory effect of trastuzumab on cell proliferation in the HER2-positive cancer cell line BT-474 (P<0.05), and the drug-induced G0/G1 block (P<0.05). Moreover, SLC25A43 influenced the percentage of Ki-67-positive cells. Our findings demonstrate that the mitochondrial protein SLC25A43 affects drug efficacy and cell cycle regulation following drug exposure in breast cancer cell lines.